Isolation, structure, and activity of -Phe-Met-Arg-Phe-NH2 neuropeptides (designated calliFMRFamides) from the blowfly Calliphora vomitoria. - Duve, H (1992)
Thirteen neuropeptides varying in length from 7 to 11 residues and ending C-terminally in -Phe-Met-Arg-Phe-NH2 (calliFMRFamides 1-13) and one dodecapeptide ending in -Met-Ile-Arg-Phe-NH2 (calliMIRFamide 1) have been isolated from thoracic ganglia of the blowfly Calliphora vomitoria. Different repeating patterns of amino acid sequences enable the peptides to be arranged into distinct groups. One such group of five nonapeptides has the sequence Xaa-Pro-Xaa-Gln-Asp-Phe-Met-Arg-Phe-NH2. Three peptides in this group, with the N-terminal tripeptide sequences Thr-Pro-Gln-, Thr-Pro-Ser-, and Ser-Pro-Ser-, are able to induce fluid secretion from the isolated salivary gland of Calliphora at a concentration of 0.1 to 1 nM. However, two other members of this group with the N-terminal tripeptide sequences Lys-Pro-Asn- and Ala-Pro-Gly-, the latter being the most abundant peptide isolated, were inactive in this assay, as were all the other peptides isolated. This indicates that the N terminus (in addition to the C terminus as previously found for FMRFamides of other organisms) is crucial for at least some biological activities.